The Campus Canopy, 1935-02-13 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1935)
Turnbull, Ambos Head S.G.A.; Service Held for Dr. J.M. Pound - Dies at Home in Athens, Georgia; Sock and Buskin Announce Play; Reverend Meeks Addresses Chapel; How We Concentrate; Dr. Punke Attends Education Meeting;
Georgia State Womans College. "The Campus Canopy, February 13, 1935." Vol.01, No.09. Valdosta State University Archives and Special Collections, 2018. http://hdl.handle.net/10428/2979. ### Persons Mentioned ### Alvata Carter; Amanda Barksdale; Ambos Turnbull; Ames Watkins; Angus Grace; Antoinette Andrews; Aubrey Stump; Barara Hatcher; Bedrew Eatman; Berkeley McKey; Bill Tullis; Broun Hutchinson; Buck Murphy; Caesar; Carl Pittman; Carolyn Greene; Carolyn Warnell; Charles Jenkins; Clara Davis Adams; Clare Lawson; Clement Green; Cleo Barber; Clyde Beal; Curtis Jack; David Copperfield; Denese Beasley; Doris Young; Dorothy Hall; J.A. Durrenberger; E. E. Meeks; Edgar Allan Poe; Eleanor Lee; Elissa Landi; Elizabeth Green; Ellie Etheridge; Emma Ruth Jones; Estelle Roberts; Ethlyn Massey; Eva Le Gallienne; Eva Mae Smith; Evelyn May; Ferenc Molnar; Frances Hiers; Franchot Tone; Frank Reade; Gary Cooper; Gayle Chute; GeDelle Brabham; Gene King; George Brent; Gerry Arrington; Gus Cleveland; H. H. Powers; Harold Gulliver; Harold Punke; Harriet Rogers; Harris Dukes; Helen Dale; Henry Kate Gardner; Henry Tullis; Herbert Frazier; Howard Cheshire; Huey Long; Hugh Carroll; Hulda Summer; Iva Chandler; J. D. Young; J. M. Pound; J. W. Martin; Jessie Langdale; Joe Daniels; John Sineath; Josephine Hutchinson; Josephine Joubert; Katherine Connell; Kathleen Burke; Kitsy Smith; Laura McLeod; Lee Stear; Leila Mae Tyson; Leila Urquhart; Leonard Baldwin; Leonora Dufour; Leonora DuFour; Lionel Barrymore; Lois Corley; Lois Hafford; Lora McPhaul; Lorene Johnson; Louie Hearn; Louise Childers; Louise Hardy; Louise Sawyer; Lucile Wurst; Manell Vincent; Margaret Berryhill; Margaret Hudson; Maria Dominica; Marie Joiner; Marie Miller; Marion Reid; Marjorie Jordon; Marshall Paulk; Martha Gardner; Martha Gardner; Martha Gay; Mary Agnes Roane; Mary Alderman; Mary Edith Grainger; Mary Elizabeth Nix; Mary Katherine Harrell; Mary Katherine Wisenbaker; Matilda Tillman; Mayme Register; Mildred Daniels; Mildred Hudson; Mildred Ogles; Mildred Turnbull; Myrna Loy; N. Patterson; Nicholas Agi; Nichols; Ola Lee Powell; Paula Sapp; Peggy Corbett; Jere Pound; Priscilla Kelley; Priscilla Kelly; Rachell Coxwell; Frank Reade; Richard Cromwell; Rudy Vallee; Rufus Wilson; Ruth Bunn; Ruth Loughridge; Ruth Williams; Sallie Prescott; Tad Whipple; Una Ritch; Upton Sinclair; J. C. Hankinson; Vasco Martin; Virginia Martin; Wade Clanton; Walter Williams; Willene Roberts; William Makepeace Thackeray; Winnie Davis; Y. W. Cabinet; Ruby Jordan; Pearl S. Buck; Buck Jones; ### Locations Mentioned ### Adel, Georgia; Blackshear, Georgia; Camilla, Georgia; Fitzgerald, Georgia; Surrency, Georgia; Athens, Georgia; Atlanta, Georgia; Cairo, Georgia; Chabar, Iran; Chicago; Clyattville, Georgia; Cordele, Georgia; Delaware; Donaldsonville, Georgia; Emory University; Florida; Folkston, Georgia; Georgia; Homerville, Georgia; Jacksonville, Florida; Jasper, Georgia; Jesup, Georgia; Knoxville; Lakeland, Georgia; Louisiana; MARTIN THEATRE; Mass.; Milledgeville, Georgia; New England; New York City; Newton; China; Quitman, Georgia; Rome, Georgia; Savannah, Georgia; Statesboro, Georgia; Tallahassee, Florida; Tennessee; Valdosta, Georgia; Virginia; W. Hill Ave., Valdosta, Georgia; Waycross, Georgia; Pearson, Georgia; ### Organizations Mentioned ### AAAB; Sock and Buskin Club; Davidson College; Eastern Standard Time; G. S. W. C.; Georgia State Womans College; HILTON; Paramount Picture; Pioneer Press; Printing Company; Revolutionary Party; Ritz Management; Supreme Court; Pan-Hellenic; Valdosta Club;
Keywords: College student newspapers and periodicals -- Georgia -- Valdosta; Georgia State Womans College -- Students -- Periodicals; Newspapers